PENGARUH STABILITAS MONETER PADA SISTEM PERBANKAN SYARIAH DI INDONESIA - Riang Giantara; Lavlimatria Esya (Media Ekonomi, 2015)
Bank is a financial institution that serves to raise funds and transfer back fund which has been collected to the public in the form of credit as well as providing services in traffic payment and distribution of money. Central Bank as monetary authorities have to do conventional monetary policy and monetary policy islam to effectively affect the situation the macro economy as a whole. This study aims to look at how the stability of the monetary system of Islamic banking in Indonesia. As well as how the impacts will occur on monetary instruments that are influenced by the instruments of macro. To get the results of this research purposes, then the analytical tools used in this study is the analysis tool Vector Auto Regression (VAR). The variables used in this study are as follows, the amount of money circulating in the narrow sense (M1/p), SWBI, exchange rate, and the GDP of the period 2008-2013 of September. Results of the analysis of these studies mention that monetary stability in the banking system of Sharia through the instruments of the money supply in the narrow sense is relatively stable